Zlateh the goat, and other stories - Singer, Isaac Bashevis, 1904-1991 (HarperCollins, 1994)
Seven tales whose roots are in middle-European Jewish folklore and legend. The characters range from children to lovers, scolding wives to henpecked husbands, patient animals to hardworking men, and devils and goblins to the fools of Chelm.